초등학생을 위한 데이터 시각화 리터러시 교육 방안 연구 - 김민정(Kim Min Jung) (한국디자인리서치, 2021)
오늘날의 아이들은 꽤 어린나이부터 온택트 사회에서 생활하며, 자연스럽게 코로나19의 현황을 나타내는 그래프, 차트 또는 지도에 노출되고 있다. 그러나 성인을 포함한 많은 아이들이 데이터시각화를 제대로 읽지 못해 그 뜻을 이해하지 못하는 경우가 많다. 따라서 본 연구는 ‘데이터시각화 교육’이 하루빨리 체계적으로 마련되어야 한다는 생각에서 출발한다. 아이들을 위한 데이터시각화 교육의 필요성을 고찰하고 접근 방향을 도출하기 위해 선행연구들과 문헌자료, 그리고 웹기반의 동영상과 학술자료를 분석하였다. 그 결과 해외의 경우 데이터시각화 리터러시 능력 향상을 위한 구체적인 실행 연구가 많았다. 국내의 경우에는 교과 중심의 데이터시각화 자료에 대한 연구와 실제 현장에서의 활용을 위한 교육 방안을 제시하였는데, 이중 잘못된 사례를 선정하거나, 지나치게 제한적인 데이터시각화 유형만을 활용하는 등, 교육 방안을 제공하는데 있어 정보디자인 및 데이터시각화 전문가에 대한 검수가 필연적으로 동반되어야 함을 알아냈다. 따라서 초등학년 아이들을 위한 데이터시각화 교육을 마련하기 위한 방안을 도출하였다. Today's children live in on-tact society from quite a young age, and are naturally exposed to graphs, charts, or maps that indicate the current status of Corona 19. However, many children, including adults, do not understand the meaning of data visualizations because they cannot properly read them. Therefore, this study begins with the idea that 'data visualization education' should be systematically prepared as soon as possible. In order to consider the need for data visualization education for children and derive approach directions, prior studies, literature, and web-based videos and academic materials were analyzed. As a result, there were many specific implementation studies abroad to improve data visualization literacy. In Korea, we presented education methods for researching subject-oriented data visualization data and actual use in the field, and found that inspection of information design and data visualization experts was inevitable in providing education methods such as selecting false cases or utilizing overly limited data visualization types. Therefore, a plan was drawn to provide data visualization education for elementary students. KCI Citation Count: 9